Global landscape of 2-hydroxyisobutyrylation in human pancreatic cancer - Lu, Yun; Li, Xiangyu; Zhao, Kai; Qiu, Peng; Deng, Zhengdong; Yao, Wei; Wang, Jianming (Frontiers in Oncology, 2022)
As a new type of post-translational modifications (PTMs), lysine 2-hydroxyisobutyrylation (Khib) was firstly identified in histones and functioned as a regulator of transactivation in mammals. However, the role of Khib proteins remains to be investigated. Here, we firstly identified 10,367 Khib sites on 2,325 modified proteins in seven patients with pancreatic cancer by applying liquid chromatography with tandem mass spectrometry (LC-MS/MS) qualitative proteomics techniques. Among them, 27 Khib modified sites were identified in histones. Bioinformatics analysis revealed that the Khib-modified proteins were mainly distributed in the cytoplasm and enhanced in metabolic pathways including glycolysis/gluconeogenesis, the citrate cycle (TCA cycle) and fatty acid degradation. In an overlapping comparison of lysine 2-hydroxyisobutyrylation, succinylation and acetylation in humans, 105 proteins with 80 sites were modified by all three PTMs, suggesting there may be a complex network among the different modified proteins and sites. Furthermore, MG149, which was identified as Tip60 inhibitor, significantly decreased the total Khib modification level in pancreatic cancer (PC), and strongly suppressed proliferation, migration and invasion ability of PC. Overall, our study is the first profiling of lysine 2-hydroxyisobutyrylome and provides a new database for better investigating Khib in PC.